A novel route for volume manufacturing of hollow braided composite beam structures. (2nd October 2019) - Singh, Anubhav; Reynolds, Neil; Carnegie, Craig R.; Micallef, Christopher; Keating, Elspeth M.; Winnett, James; Barnett, Alastair E.; Barbour, Steve K.; Hughes, Darren J.
Abstract: This work investigates the application of a rapid variothermal moulding process for direct processing of a braided thermoplastic commingled yarn. The process uses locally controllable, responsive tooling which provides opportunities for optimum part quality and significantly reduced cycle times compared with conventional processes. The proposed process was used to directly manufacture hollow beam structures from dry commingled braided preforms. It was demonstrated that the cycle time using the rapid process was reduced by more than 90% as compared to a conventional bladder moulding process, resulting in a total cycle time of 14 min. Additionally, initial three point flexure test results indicated an improvement in the mechanical performance of the resultant parts as compared to the benchmark. Graphical Abstract: